PERAN INOVASI PRODUK DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF UMKM BERBASIS KERAJINAN - Nasir, Nasir (Universitas Tanjungpura, 2025)
Product innovation is one of the important strategies in increasing the competitiveness of Small and Medium Enterprises (SMEs) in the midst of increasingly fierce global competition. This study aims to analyze the role of product innovation in increasing the competitiveness of handicraft SMEs in Makassar City. The research method used is a qualitative approach with in-depth interview techniques and observations of 15 handicraft SMEs. The data obtained were analyzed using thematic methods to identify patterns and key findings. The results of the study show that product innovation, especially those that combine traditional design elements with modern styles, is able to increase the added value of products in the local and international markets. In addition, the use of environmentally friendly raw materials provides a significant competitive advantage, in line with the increasing demand for sustainable products. The implementation of digital technology, such as social media and e-commerce, also helps SMEs in marketing products more widely and efficiently. However, there are obstacles in the implementation of innovation, such as limited capital, low human resource skills, and low awareness of local consumers towards innovative products. This research emphasizes the importance of product innovation in building the competitiveness of SMEs, as well as providing recommendations for increasing government and private sector support in overcoming existing challenges. This finding is expected to be a reference in the development of SME product innovation strategies in the future.